2015
DOI: 10.1080/15374416.2015.1055858
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association of Youth Attention-Deficit/Hyperactivity Disorder and Anxiety With Delinquency and Aggression

Abstract: Although attention-deficit/hyperactivity disorder (ADHD) is independently associated with both anxiety and conduct problems, it is unclear how co-occurring ADHD + anxiety are associated with different forms of conduct problems. That is, there is relatively little evidence how ADHD and co-occurring anxiety, relative to ADHD only and anxiety only, are associated with aggression and delinquency. Controlling for age, sex, oppositional defiant disorder diagnostic status and total psychopathology, we compared childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Finally, many of the arguments of the current study also apply to the impulsive behaviours observed in conduct disorder (CD) and oppositional defiant disorder (ODD), both also strongly correlated with ADHD symptoms (e.g. Falk et al, 2015). Therefore, a potentially interesting extension to the current study would be to conduct analogous tests of the developmental relations between the impulsive versus non-impulsive behaviours beyond aggression associated with CD and ODD.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, many of the arguments of the current study also apply to the impulsive behaviours observed in conduct disorder (CD) and oppositional defiant disorder (ODD), both also strongly correlated with ADHD symptoms (e.g. Falk et al, 2015). Therefore, a potentially interesting extension to the current study would be to conduct analogous tests of the developmental relations between the impulsive versus non-impulsive behaviours beyond aggression associated with CD and ODD.…”
Section: Discussionmentioning
confidence: 90%
“…In a large community-based sample of children, Cuffe et al (2015) found that trouble with police, school suspensions, and school expulsion were equally associated with ADHD and ADHD with an ANX/mood disorder. Falk et al (2015; see above) also found that children with ADHD and co-occurring ANX were neither more nor less delinquent that those with ADHD alone. During free play, Pollack et al (2016; see above) found no difference in observed negative verbal/physical behavior among children with ADHD alone or ADHD with ANX.…”
Section: Co-occurring Anxiety Has No Effect On Cpsmentioning
confidence: 92%
“…Becker et al, 2012;Bloemsma et al, 2013;Falk et al, 2015;Sørensen et al, 2011). For example , Falk et al (2015) found evidence consistent with attenuation. In a sample of 380 youth aged 5 to 17, they found that those with both ADHD and anxiety showed significantly lower levels of aggression than those with ADHD only.…”
Section: Introductionmentioning
confidence: 92%
“…Among the small number of studies that have reported relevant data, results are mixed with respect to which, if either, is supported (e.g. Becker et al, 2012;Bloemsma et al, 2013;Falk et al, 2015;Sørensen et al, 2011). For example , Falk et al (2015) found evidence consistent with attenuation.…”
Section: Introductionmentioning
confidence: 99%